Work-life balance in US law using the example of California - Wioletta Witoszko (Review of European and Comparative Law)
In the United States, parents’ entitlements, including the right to childcare leave, are regulated primarily by federal law and state law. An example of a state law, which is discussed in this paper, is the law of California, which is one of the leading states in terms of worker rights. The implementation of a work-life balance policy in California is mainly focused on extending childcare leave entitlements, guaranteeing that this leave is paid, enabling flexible work arrangements and facilitating the use of these entitlements by men.